The Effect of Project-Based Learning E-Modules on Student Competence in Developing Science Process Skills Assessment Instruments - Ramlawati Ramlawati; Nur Indah Sari; Rifda Nurhikmawati Arif; Nurul Ilmi (Universitas Syiah Kuala, 2025)
Student competence in developing assessment instruments is crucial for ensuring the quality of learning evaluation. This research aims to determine the effect of project-based learning e-modules on student competence in developing science process skills instruments. This study employed a quasi-experimental research design with a nonequivalent control group. The sample was selected using purposive sampling based on students' initial abilities, resulting in 54 students divided into two groups. Data collection instruments included the development of one basic and integrated SPS question by students for each indicator. The research data were analyzed using a t-test with a significance level of 5%. The results demonstrated a significant positive effect of the PjBL e-module on student competence in developing SPS instruments, with the experimental group's average competence being 77.36, which was higher than the control group's average of 62.41. This research is expected to improve the competence of prospective science teachers in developing valid and effective assessment instruments, thereby addressing obstacles such as a lack of understanding of SPS, difficulties in constructing complex questions, and challenges in creating effective distractors